Pendapatan dan Kelayakan Usaha Peternak Ayam Pedaging Mitra - Merry Dawapa; Nina Maksimiliana Ginting (Musamus Journal of Livestock Science, 2021)
This study aims to analyze the income and business feasibility of partner broiler breeders. This research was conducted in Merauke District. The location selection was done purposively. Sampling in this study uses the census method. Respondents in this study were 13 partner broiler breeders. The analysis technique used is the analysis of costs, revenues, income and feasibility. The results showed that the total cost incurred was IDR 38,206,730 with a revenue of IDR 42,481,153.85 and an income of IDR 4,274,423.77. This partner broiler breeder business is said to be feasible with an R / C of 1.10, which is greater than 1.